Death, family and the law : the contemporary inquest in context - Kirton-Darling, Ed (Bristol : Bristol University Press, 2023)
When a death is investigated by a coroner, what is the place of the family in that process? This accessibly written book develops a nuanced analysis of the contemporary inquest system in England and Wales.
Previously issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 9, 2023).
Keywords: Coroners -- England; Coroners -- Wales; Dead -- Family relationships; Law; Laws of specific jurisdictions & specific areas of law